Tafsir Maqasidi - Muhammad Ainur Rifqi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Almost all scholars agree that every law of Sharia, in it must be tucked into a noble purpose, namely to bring Mashlahah and reject Mafsadah. And Mashlahah itself is the main purpose of Maqasid al-Shari'ah. As a final destination, Maqasid al-Shari'ah occupies an important position as a benchmark or indicator of a legal problem that is charged Mashlahah or Mafsadah in the determination of Islamic law. Imam al-Shatibi stated that the disagreements among scholars' many are caused by their mastery over the Maqasid al-Shari'ah or even incomprehension their upper Maqasid al-Shari'ah. This statement indicates the strategic position of Maqasid al-Shari'ah in the historicity of the development of Islamic teachings and its various aspects, no exception to the science of Tafsir.